LOAD DISTRIBUTION ON SOIL PROFILE AS GENERATED BY FARM MACHINERY TIRES - ALBIERO, Daniel; Maciel, Antonio Jose da Silva; Dal Fabbro, Inácio Maria (Revista Brasileira de Engenharia de Biossistemas, 2008)
Soil compaction is considered as a major agricultural problem which is close associated to agricultural productivity. This way, the sources of soil compaction should be identified and conveniently studied, so the interacting factors can be considered to propose a future mathematical model. Great part of Brazilian tractors is equipped with tires, which are recognized to generate soil compaction. This research work proposes the application of the shadow Moiré technique to map strain distribution on soil profile as well as density increase due to the action of loads generated by tractor tires. Iso-strain curves generated from more fringes.